Manajemen Kurikulum Pengembangan Pribadi Muslim Pada Mata Pelajaran Pendidikan Agama Islam - Zahrotul Azkiya' Azizah; Bahrozi, Imam; Bisri, Muhammad (Program Studi Pendidikan Agama Islam, 2023)
The curriculum is a set of plans and arrangements regarding the content and learning materials as well as the methods used as guidelines for organizing teaching and learning activities. Therefore, the curriculum must be planned well to facilitate the achievement of teaching objectives, this arrangement is called curriculum management. The Muslim Personal Development Curriculum at SDI Al Azhar is a modification and combination of the National Curriculum plus the characteristics of Al Azhar. The KPPM curriculum covers all subjects, especially Islamic Religious Education subjects. The KPPM curriculum still sounds foreign to the public's ears, so sometimes this curriculum is underestimated, so many people ask how the learning activity process starts from planning, implementation and evaluation. To find out this information, researchers carried out research methods in the form of observation, interviews and documentation using a qualitative approach. The results of this research show that the KPPM curriculum management process for PAI subjects through the planning, implementation and evaluation stages is running well. The planning stage is carried out by all teachers with teachers compiling Prota, Prosem, educational calendars, lesson schedules, etc. At the implementation stage, each teaching staff carries out tasks according to the planned tasks, the teacher makes a lesson plan based on the syllabus as the material to be taught. Next there is an evaluation stage starting from the school, the principal, teachers and students carry out this stage to find out whether they have achieved the specified target or not.